Tibial Tubercle Fracture in a 14-Year-Old Athlete with Bilateral Lower Pole Bipartite Patella and Osgood-Schlatter Disease - Fabio Pascarella; Antonio Ziranu; Giulio Maccauro (Case Reports in Orthopedics)
We present a case of tibial tubercle fracture in a young male athlete with both bilateral bipartite patella at the lower pole (Saupe type I) and Osgood-Schlatter disease. Open reduction and internal fixation were performed to restore the extensor mechanism of the knee.